2011
DOI: 10.1016/j.lwt.2010.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Rheological, textural and microstructural features of probiotic whey cheeses

Abstract: a b s t r a c tWhey cheeses have been manufactured with probiotic bacteria e viz. Bifidobacterium animalis Bo and Lactobacillus casei LAFTI Ò L26, from combinations of bovine whey and milk, following protein denaturation at 90 C; they were subsequently inoculated (at 10%) with those strains, and homogenized afterwards; additives such as salt and sugar were then incorporated; and the resulting solid matrices were stored at 7 C for up to 21 d. Oscillatory measurements and instrumental texture profile analyses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 15 publications
2
6
0
1
Order By: Relevance
“…These results confirmed the technological application of fresh whey from Minas Frescal cheese as a means to develop probiotic bacteria (Almeida et al, 2008(Almeida et al, , 2009. Moreover, our findings were comparable to those of other studies involving dairy beverages (Madureira et al, 2010) and to results obtained for other dairy products processed from cheese whey (Madureira et al, 2005(Madureira et al, , 2008(Madureira et al, , 2011a and other dairy foods, such as yogurts (Cruz et al, 2012), cheese (Gomes et al, 2011;Escobar et al, 2012), and ice cream (Di Criscio et al, 2010;Ferraz et al, 2012).…”
Section: Ph and Microbiological Valuessupporting
confidence: 90%
“…These results confirmed the technological application of fresh whey from Minas Frescal cheese as a means to develop probiotic bacteria (Almeida et al, 2008(Almeida et al, , 2009. Moreover, our findings were comparable to those of other studies involving dairy beverages (Madureira et al, 2010) and to results obtained for other dairy products processed from cheese whey (Madureira et al, 2005(Madureira et al, , 2008(Madureira et al, , 2011a and other dairy foods, such as yogurts (Cruz et al, 2012), cheese (Gomes et al, 2011;Escobar et al, 2012), and ice cream (Di Criscio et al, 2010;Ferraz et al, 2012).…”
Section: Ph and Microbiological Valuessupporting
confidence: 90%
“…paracasei. This improvement of cheese firmness by decreasing pH has been reported in different researches such as Farahnaky et al (2013) in Iranian UF cheese, Madureira et al (2011) in probiotic whey cheese, Souza and Saad (2009) in probiotic Minas Fresh cheese. Cleaved peptides become a part of the serum phase and cannot contribute to the structure of cheese resulting in lower hardness amounts (Lucey et al 2003).…”
Section: Hardnesssupporting
confidence: 70%
“…On the other hand, probiotic strain was also effective on hardness. Madureira et al (2011) demonstrated that L. casei containing cheese was firmer than other samples. As shown in Fig.…”
Section: Hardnessmentioning
confidence: 97%
“…Los materiales duros se caracterizan porque a una gran fuerza de cizalla produce una deformación relativamente pequeña, mientras que para materiales blandos una gran fuerza de cizalla produce una gran deformación 20 . El queso fresco y el queso con 10% de suero concentrado presentaron una deformación pequeña por lo que fueron considerados quesos blandos y los quesos obtenidos con 20%, 30% y 50% de suero concentrado tuvieron características de quesos blandos débiles, de apariencia cremosa y bajos en grasas (ver tabla 3); éstas últimas son parecida a una tipo de queso elaborado con suero de leche bajo en grasa 21 . CONCLUSIONES Fue posible la elaboración de queso fresco utilizando suero concentrado por ultrafiltración (presión de 2,5 bar, temperatura de 25°C, tamaño de filtro de 50 nm y un factor de retención volumétrica de 2).…”
Section: Propiedades Reológicas Del Quesounclassified